2018
DOI: 10.3390/nano8070526
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible Light Driven Photocatalytic Behavior of BiFeO3/Reduced Graphene Oxide Composites

Abstract: BiFeO3/Reduced Graphene Oxide (BFO/RGO) composites have been fabricated by a simple hydrothermal method. The X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman, and X-ray photoelectron spectroscopy (XPS) analysis reveal that graphene oxide was reduced in hydrothermal process and BFO/RGO composites were successfully synthesized. UV-visible absorption and photoluminescence properties show that the introduction of RGO can effectively reduce the recombination of photogenerated electron and hole pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…It has been reported that the super-exchange interaction between Fe 3p and O 2p ions plays an important role in the ferromagnetic properties of BFO. The ferroelectric properties stem from the off-center displacement of 6 s2 lone pair electrons of Bi 3+ ions [ 6 , 7 ]. Meanwhile, the potential magnetoelectric coupling effect in BFO has also attracted much attention [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the super-exchange interaction between Fe 3p and O 2p ions plays an important role in the ferromagnetic properties of BFO. The ferroelectric properties stem from the off-center displacement of 6 s2 lone pair electrons of Bi 3+ ions [ 6 , 7 ]. Meanwhile, the potential magnetoelectric coupling effect in BFO has also attracted much attention [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in good agreement with previous results reported in the literature concerning photocatalytic degradation efficiency of MFO/rGO composite layers. The inclusion of rGO improved the photocatalytic activity, demonstrating considerably better degradation of methylene blue [77] or Rhodamine B [20] dye molecules and higher hydrogen production by water-splitting, as compared to pure BiFeO 3 [77]. The photocatalytic properties of the LFO/rGO composite photocatalyst containing 5 wt.% rGO, with the highest degradation efficiency under UV light irradiation, were also tested during visible light irradiation (Figure 8).…”
Section: Photocatalytic Degradation Of Methyl Orangementioning
confidence: 99%
“…Photocatalytic technology has been used as a kind of green environmental treatment. However, the use of semiconductor photocatalytic materials such as TiO 2 and ZnO can only be used in the UV light only accounted for less than 5% parts of the solar light [3,4]. The exploring of visible-light photocatalytic materials is a hotspot among materials and chemical scientists.…”
Section: Introductionmentioning
confidence: 99%